Frequency of multidrug, extensively drug and pandrug-resistant bacteria isolated from external otitis and dermatitis in dogs - Manrique Valentín, María del Carmen (2021)
The increase in multi-drug resistance of bacteria from animals has been registered worldwide. The aim of this study was to report the frequency of multidrug-resistant (MDR), extensively drug-resistant (XDR) and pandrug-resistant (PDR) bacteria isolated from external otitis and dermatitis in dogs. A total of 587 antimicrobial susceptibility records were analyzed between 2014 and 2017 from pets that were examined at an University Veterinary Clinic in the northeast of Lima, Perú. Antimicrobial susceptibility was determined by disk-diffusion method according to the Clinical Laboratories Standards Institutes breakpoints.